Servicios de apoyo online a víctimas: a propósito del artículo 25.2 de la Directiva (UE) 2024/1385 del Parlamento Europeo - Romero-Seseña, Pablo (Revista de victimología, 2024)
Violence against women and domestic violence are pervasive global issues necessitating a comprehensive and effective response. Directive (EU) 2024/1385 of the European Parliament and Council underscores the critical role of victim support services, emphasizing the need for both physical and online accessibility. This study examines the evolution and efficacy of online support mechanisms for crime victims, particularly in the context of violence against women and domestic violence. A systematic literature review and case study analysis reveal significant strengths, such as enhanced accessibility and the provision of anonymity, as well as notable weaknesses, including the lack of personal contact and technological barriers. Special attention is given to evaluating these services’ effectiveness based on the limited empirical evidence available. In light of Directive 2024/1385 and Directive 2012/29 on victims’ rights, this study offers a series of recommendations for the design and implementation of online support services. These recommendations aim to ensure compliance with legal requirements and address the broader needs of victims. The findings contribute to the ongoing discourse on improving victim support services and highlight the need for further empirical research in this area.